STUDENTS’ AFFECTIVE REACTION TOWARD USING G-SUITE MEET FOR EDUCATION IN LEARNING ENGLISH SPEAKING (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This qualitative descriptive study aims to expose the students’ affective reactions after learning speaking through G-Suite Meet as one of G-suite for education features. This also confirms do affective reactions support the enhancement of students’ speaking performance and can this featured be maintained in the future? The respondents of this study were twenty students of SMA Negeri 3 Palu and three of them were as informants. They are chosen as the subject of this study because their English speaking class is conducted in Google meet. In collecting the data, 13 points of questionnaires in term of likert scale and four interview questions in term of semi- structured had been distributed. The responses of the students were displayed using frequency and percentage on the table and then it was described, interpreted and concluded. The information of the interviewees was limited to describe the scope of this study. The results of this study convey that the students expose positive reactions related to the use of G-suite features in term of Google meet to bridge learning speaking. The positive reactions also support the enhancement of students’ speaking performance. However, this study showed a phenomenon that some students do not show significant enhancement related to their performance. In addition, this study also informs that although students confirm positive reaction and the students also show improvement related to their speaking performance, learning speaking through Google meet cannot be regularly maintained, it only stands for urgent situation because conducting learning through Google meet are claimed not optimal.